Perhubungan sosial dan kesan stigma wanita lewat berkahwin - Nur Fazlin Shazana, Binti Mohamad Safiai (Faculty of Cognitive Sciences and Human Development., 2008)
This research aims to study about unmarried women in terms of social relation among families, friends and the society. Furthermore, this research aims to identify the types of stigma that has been received by the unmarried women as well as the positive and negative effects of it. Three participants between the age of 35 to 50 years old and unmarried were chosen to participate in this research. This research used semi-structured interview, observation by using journal of self reflection and audio recording in collecting the data. Data were analyzed using three processes; which are cleaning, understanding and analyze into sub-concept. The results indicated that the social relations of the unmarried women were in normal condition although their social relations were limited because of the work load in their carriers. In addition, the result of this research illustrated that there are many types of stigma which have been received by the unmarried women. Therefore, the positive and negative effects of it had existed. In spite of it, the participants are able to build their own motivation which had encouraged them to be more successful in their life. The implications and future suggestions of this study were further discussed.